0176 Sinonasal cancer following occupational styrene exposure: a new signal of human carcinogenesis?. (21st August 2017) - Nissen, Mette Schou; Stokholm, Zara Ann; Christensen, Mette Skovgaard; Schlünssen, Vivi; Vestergaard, Jesper Medom; Iversen, Inge Brosbøl; Kolstad, Henrik Albert
Abstract : Objective: We recently suggested an increased risk of sinonasal cancer following occupational styrene exposure. The objective of the current study is to explore this finding further by including information on quantitative measures of styrene exposure and histological information on sinonasal cancer subcategories. Methods: We followed 73 092 workers employed in 456 small and medium sized Danish reinforced plastics companies from 1968 to 2011. Incident cases of sinonasal cancer were identified by linkage with the national Danish Cancer Registry. We modelled cumulative styrene exposure level from historical styrene measurements, company information, and survey data and estimated rate ratios (RR) of overall sinonasal cancer and histological subcategories. Due to few cases, these analyses were performed with no adjustment. To account for potential confounding from age, gender and employment in wood industries we conducted a nested case-control study matched on these factors. Analyses were performed with conditional logistic regression. Results: The RR of overall sinonasal cancer (37 cases) was doubled in the upper exposure tertile compared to the lower exposure tertile. For adenocarcinomas (9 cases), the RR in the medium and upper exposure tertiles were 1.17 (95%CI 0.07–18.72) and 7.87 (95%CI 0.97–63.94), respectively. Comparable results were obtained from the case-control analysis indicating limited confounding by age, gender and wood dust exposure. No consistent trend was observed for squamous cell carcinomas. Conclusion: Despite statistically non-significant results and limitations owing to the few cases, this study indicates increased risk of sinonasal adenocarcinomas among high level styrene exposed workers and could signal a carcinogenic effect of styrene.